Pelatihan Produksi Energi Ramah Lingkungan Berbasis Limbah Buah-Buahan sebagai Upaya Mewujudkan Desa Mandiri Energi di Desa Babussalam, Rokan Hulu - M. Alkadri Perdana; Johny Custer; Andri Nofiar. Am; Larbiel Hadi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to improve the knowledge and skills of residents in Babussalam Village, Rokan Hulu Regency, in processing fruit waste into environmentally friendly energy through simple pyrolysis technology. The activity addresses the abundance of unutilized fruit waste that potentially causes environmental pollution. Conducted on October 30, 2025, with 20 participants from the local community and BUMDes Babussalam, the activity employed participatory methods including socialization, technical training, and ongoing mentoring. Results showed an 85% understanding level of renewable energy, based on pre-test and post-test evaluations improving from 45% to 85%. Participants successfully produced bio-oil and activated charcoal through direct pyrolysis practice using equipment developed from applied research. A village working group was also established under BUMDes Babussalam coordination to develop self-sufficient energy initiatives. The activity proves that integrating applied research, appropriate technology, and community participation creates an effective model for community-based energy empowerment, supporting national energy security and Sustainable Development Goals, particularly Goal 7 on clean energy and Goal 11 on sustainable communities.